Indonesian Learning: Towards the Academic Achievement of Communicative Competence - Mega Febriani Sya; Helmia Tasti Adri; Abdul Kholik; Deski Halim Sudjani; Zahra Khusnul Lathifah; Uslan (Indonesian Journal of Social Research (IJSR), 2021)
Academic achievement becomes very important in the language learning process. Student performance, student progress and student potential are essential to measuring academic achievement or learning outcomes. This study aims to identify the relationship of final learning achievement with the student learning experience to improve students’ language skills. Research focuses on what skills are the final achievements of learning and observe whether the learning experience can support the plan of acquisition of learning achievements. Research design is qualitative content analysis. The population used is the semester learning plan document of the Indonesian language and literature learning model SD. Sample selection uses the method of sampling units by selectively distinguishing the units to be analyzed based on the scope of the research problem. Data analysis using interpretive approaches: Reducing data to manageable representations: summarizing or simplifying data; inferring contextual phenomena: relying on analytical constructs or models of the chosen context as warrants; Narrating the answers to content analysts’ questions amount to make the result comprehensible to others. Based on the study results, the learning experience is determined based on the end goal of learning. Discuss in-depth the concept of learning the Indonesian language and literature in elementary schools based on multiliterate, integrative, and differentiated learning concepts.